A clinico-epidemiological study of mask induced facial dermatoses due to increased mask usage in general public during COVID-19 pandemic - A., Ramesh; K., Thamizhinian (International Journal of Research in Dermatology, 2021)
Background: Since the beginning of COVID-19 pandemic many people started experiencing facial dermatoses like acne due to prolonged mask use and other personal protective equipment’s. Though most of the facial dermatoses due to face mask are reported in healthcare workers, general public are also affected by facial dermatoses due to prolonged mask use. Hence, we decided to undergo a study on different patterns of facial dermatoses due to prolonged mask use in Rajiv Gandhi government general hospital, Chennai. Aim of the study was to find out the incidence of facial dermatoses due to prolonged mask use in general public in the OPD of department of DVL in MMC and RGGGH, Chennai. Methods: This is a cross sectional study conducted at RGGGH during the months august, September and October 2020. The clinico-epidemiological details were collected from 400 patients attending the OPD of department of DVL at MMC and RGGGH. Results: Among 400 study participants with mask induced facial dermatoses, acne (Maskne) was the most common facial dermatoses detected in 43% of participants, followed by Seborrhoea (28%), frictional dermatitis (18%), contact dermatitis (16%), non-specific erythema, cheilitis and other conditions. Conclusions: Mask induced facial dermatoses can occur due to various factors like occlusive effect of mask, hyperhydration, seborrhoea, ambient high humidity due to sweating. As mask usage cannot be abandoned completely due to risk of virus transmission, dermatologists must be aware of the preventive strategies and treatments for mask induced facial dermatoses.